Numerical Study on Flow Physics of Damaged Vane Trailing Edge - B Thammachote; J Premyothin; S Khumhaeng; D Tanpradit; D Dipasquale; P Prapamonthon (My University, 2024)
Abstract According to practical applications in gas turbines, the turbine’s nozzle guide vane (NGV) is the first downstream component of the combustor that experiences high thermal loads from burned gases. This situation can severely damage the vane material, particularly the trailing edge (TE). This is because of the limitation of TE thickness and the difficulty of effective cooling in that region. Moreover, the deterioration of the TE surface leads to vane fatalities and has a negative impact on turbine performance because the flow field is unfavorably changed during the operation. This paper aims to numerically study the flow physics of a damaged vane TE using a 3D steady-flow CFD simulation with the SST k-turbulence model. Under the assumptions of ideal gas and compressible flow, air is used as the burned gas. To simplify the vane damage shape, the broken pattern at the TE is given in a long cutback geometry in the simulation. Numerical results in terms of turbulent kinetic energy (TKE), vorticity magnitude, turbulent viscosity, and streamlines are compared and discussed. The interesting findings show that with the inclusion of the damaged TE, the TKE and turbulent viscosity in the broken region increase dramatically on both the midspan and vertical planes. Furthermore, an increment in the vortex size is observed on the midspan plane. However, the vortex centers along the broken region disappear and are replaced by smooth streamlines.
Keywords: Trailing edge; Turbomachinery Performance and Optimization